Analysis of the Cost of Maintaining Broiler Chickens with Herbal Feed - Subhan Effendi; Ummul Masir; Ilham Ahmad; Mariani (Indonesian Journal of Contemporary Multidisciplinary Research, 2023)
The development of the broiler farming industry is currently facing many challenges such as high feed prices, management, and livestock diseases. Colibacillosis is a disease that is often found in the field so that it has an impact on the farmer's economy. Colibacillosis can cause growth disturbances, decrease in production, increase in the number of rejected chickens, decrease in carcass and egg quality, as well as chick quality (DOC) (Tabbu, 2000). The anticipatory measure is the administration of antibiotics, however their use has recently begun to be reduced due to the impact on chicken carcasses. This study aims to analyze the costs incurred for maintaining the health of livestock fed herbal feed and the cost efficiency used in raising broilers with herbal feed compared to conventional methods. The results showed that the application of herbal feed in broiler farms was efficient in saving maintenance costs